Reflections of a transborder anthropologist : from Netzahualcóyotl to Aztlán - Vélez-Ibañez, Carlos G., 1936- (The University of Arizona Press, 2020)
"Taking us on a journey of remembering and rediscovery, anthropologist Carlos G. Velez-Ibáñez shares an important look at his development as a scholar and in so doing the development of an interdisciplinary field of transborder anthropology"--